ANALISIS PENINGKATAN KOMPETENSI DAN PROFESIONALITAS PENDIDIK - Afrizen Afrizen; Elvi Syoviana; Sufyarma Marsidin; Nurhizrah Gistituati (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
educators have a strategic role in learning and have a very strong function in creating the next generation. Whether or not an education is qualified depends on the educator.therefore an educator must have the ability and professionalism in carrying out the task. And this is not separated or in accordance with the rules and laws that apply. The purpose of this study is to analyze about the improvement of competence and professionalism of teachers.the methods used in the research are qualitative with a descriptive approach. While the results of the research that is known by the existence of a rule governing the implementation of improved skills educators, an educator more active and creative later and educators will have extensive knowledge to achieve educational goals..